On a px-Biharmonic Kirchhoff Problem with Navier Boundary Conditions - Hafid Lebrimchi; Mohamed Talbi; Mohammed Massar; Najib Tsouli (Abstract and Applied Analysis)
In this article, we study the existence of solutions for nonlocal px-biharmonic Kirchhoff-type problem with Navier boundary conditions. By different variational methods, we determine intervals of parameters for which this problem admits at least one nontrivial solution.